Corporate Taxes, Patent Shifting and Anti-Avoidance Rules: Empirical Evidence - Martina Baumann; Tobias Böhm; Bodo Knoll; Nadine Riedel (Center for Economic Studies and ifo Institute (CESifo), 2018)
We empirically assess international corporate tax avoidance by strategic location of innovative output. The analysis draws on the universe of patent applications to the European Patent Office linked with data on multinational entities (MNEs) in Europe. Four findings emerge: Firstly, patent holdings are distorted towards low-tax countries. Secondly, patent location in low-tax countries is correlated with a geographic separation of R&D output and input. Thirdly, MNEs systematically sort high-value (low-value) patents to low-tax (high-tax) countries. Fourthly, the propensity to locate patent ownership in low-tax countries is significantly decreased if controlled foreign company rules are enacted in the MNE's parent country. The tightening of transfer pricing legislations, in turn, exerts a weak negative effect on the location of patent ownership only.
Keywords: H30; H70; J50; 330; corporate patents; patent taxation; profit shifting; anti-avoidance rules